Effect different level of illumination on color vision testing among colour vision deficiency patient / Nor Fatimawati Ghazali - Ghazali, Nor Fatimawati (Faculty of Health Sciences, 2015)
Colour vision testing is one of the entrance test conducted by optometrists to differentiate between normal colour vision and colour vision anomalies. However different level of illumination can affect results of colour vision testing. The objective of this study is to identify the effect of different levels of illumination on Farnsworth D-15 colour vision test among subject with colour vision defect that came to Ui Vision Care Optometry Clinic UiTM Puncak Alam Campus. Thirty subjects were participates on this study. Each subject was been screened with Ishihara colour vision and VA test. However, seven subjects from the participants who had VA 6/6 and fail Ishihara were been tested using Farnsworth D-15 at range of 30 to 36 lux, 293 to 305 lux, 905 to 920 lux and 1893 to 1910 lux of illumination. The used of low illumination which is range from 30 to 36 lux shows 28.6% of normal and deutan result respectively but 42.9% of the subject are scotopic. For moderate level of illuminations which are from 293 to 305 lux, 57.1% of subject shows normal result, 42.9% of subject shows deutan result and no result of scotopic. Then, 57.1% of subject shows normal result, 42.9% of subject shows deutan result and no result of scotopic for range 905 to 920 lux and 1893 to 1910 lux indicated for high illumination. In conclusion, colour deficiency patient can be misclassified in low illumination whereas in moderate and high level of illumination, result of Farnsworth D-15 test is the same as the standard illumination.